The Ra<U+00CC><U+0084>ma<U+00CC><U+0084>yan<U+00CC>Đa of Va<U+00CC><U+0084>lmi<U+00CC><U+0084>ki: An Epic of Ancient India, Volume IV : Kiskindhaka<U+00CC><U+0084>n<U+00CC>Đd<U+00CC>Đa - Vālmīki (Princeton library of Asian translations., 2016)
This is the fourth volume of a translation of India's most beloved and influential epic tale--the Ramayana of Valmiki. As befits its position at the center of the work, Volume IV presents the hero Rama at the turning point of his fortunes. Having previously lost first his kingship and then his wife, he now forms an alliance with the monkey prince, Sugriva. Rama needs the monkeys to help him find his abducted wife, Sita, and they do finally discover where her abductor has taken her. But first Rama must agree to secure for his new ally the throne of the monkey kingdom by eliminating the reigning king, Sugriva's detested elder brother, Valin. The tragic rivalry between the two monkey brothers is in sharp contrast to Rama's affectionate relationship with his own brothers and forms a self-contained episode within the larger story of Rama's adventures. This volume continues the translation of the critical edition of the Valmiki Ramayana, a version considerably reduced from the vulgate on which all previous translations were based. It is accompanied by extensive notes on the original Sanskrit text and on several untranslated early Sanskrit commentaries.